NEW DESIGN OF THE SOCKET OF HIP DISARTICULATION PROSTHESIS - Yaren SACHIR; Ionel SIMION (Journal of Industrial Design and Engineering Graphics, 2023)
The main goal of a lower limb prosthesis is to fulfill the functions of the missing limb such as structure and aesthetics. Among all the lower limb prostheses, the one of hip disarticulation represents a great challenge due to problems of making and accommodating the patient using it. After trying to make a classic hip disarticulation prosthesis, it is noticeable how difficult it is to use. This paper aims to create a new optimized and improved hip disarticulation prosthesis focusing on the socket but also on functionalities and on its design.